The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1515/bot-2017-0020
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular characterization of Hapalospongidion gelatinosum, Hapalospongidiaceae fam. nov. (Ralfsiales, Phaeophyceae) from Mexico

Abstract: The morphology of the crustose brown alga

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Our multigene sequence analyses revealed the genetic differences in rbcL gene sequences (9.8-11.8%) and COI-5P gene (30.0-34.3%) between Sungminia and Mesospora, while in rbcL gene sequences (9.6-13.9%) and between Sungminia and other genera within the Ralfsiales, respectively. As a comparison, families recognized within the Ralfsiales differed by ≧9.7% in the rbcL gene (Le on- Alvarez et al 2017, Parente et al 2021. We propose that Sungminia can be recognized as the basis for a new, higher-level taxon within the Ralfsiales.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Our multigene sequence analyses revealed the genetic differences in rbcL gene sequences (9.8-11.8%) and COI-5P gene (30.0-34.3%) between Sungminia and Mesospora, while in rbcL gene sequences (9.6-13.9%) and between Sungminia and other genera within the Ralfsiales, respectively. As a comparison, families recognized within the Ralfsiales differed by ≧9.7% in the rbcL gene (Le on- Alvarez et al 2017, Parente et al 2021. We propose that Sungminia can be recognized as the basis for a new, higher-level taxon within the Ralfsiales.…”
Section: Discussionmentioning
confidence: 85%
“…The Ralfsiales has been recognized by emended morphological characters: (i) discoid early development of the thallus, (ii) one to several plate-or cup-shaped chloroplasts without pyrenoids, (iii) plurangia with sterile terminal cell (s) and terminal unangia and (iv) presence of crustose gametophytic or sporophytic stages in their life history (Lim et al 2007). The classification system of the Ralfsiales at the familial level has been added and revised several times (Tanaka and Chihara 1982, Lim et al 2007, Le on-Alvarez et al 2017, Parente et al 2021.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A taxonomic study about crustose Ralfsiaceae from Korea has been carried out by combining molecular and morphological approaches (Oteng'o and Won 2020). Recent taxonomic studies on crustose brown algae in Canada, Indonesia, Japan, and Mexico indicated their great potential in diversity not only at the species level but also at the genus and family levels (Lim et al 2007, Poong et al 2013, León-Álvarez et al 2017, Parente and Saunders 2019, Parente et al 2021. Because Korea has been known as a potential hotspot of seaweed diversity for the species and generic level (Yang et al 2020), continuous surveys about crustose brown seaweeds will contribute to the expansion of our knowledge of species diversity and ecological knowledge.…”
Section: Conflicts Of Interestmentioning
confidence: 99%